Enhanced growth-driven stepwise inducible expression system development in haloalkaliphilic desulfurizing Thioalkalivibrio versutus. (September 2019) - Sharshar, Moustafa Mohamed; Samak, Nadia Abdrabo; Hao, Xuemi; Mu, Tingzhen; Zhong, Wei; Yang, Maohua; Peh, Sumit; Ambreen, Sadaf; Xing, Jianmin
Graphical abstract: Highlights: Fed-batch culturing strategy was studied in Thiolakalivibro versutus D306. Maximal growth rate and biomass production were improved by 1.6 fold and 3-fold, respectively. Preferred desulfurization product, sulfur, reached 49% in yield percent and 30 µm in diameter. Inducible regulation system was built using fed-batch coupled with DBTV approach. MazF toxin was expressed successfully from the inducible regulation system built. Abstract: Highly toxic and flammable H2 S gas has become an environmental threat. Because of its ability to efficiently remove H2 S by oxidation, Thioalkalivibrio versutus is gaining more attention. Haloalkaliphilic autotrophs, like the bio-desulfurizing T. versutus, grow weakly. Weak growth makes any trial for developing potent genetic tools required for genetic engineering far from achieved. In this study, the fed-batch strategy improved T. versutus growth by 1.6 fold in maximal growth rate, 9-fold in O.D600 values and about 3-fold in biomass and protein productions. The strategy also increased the favorable desulfurization product, sulfur, by 2.7 fold in percent yield and 1.5-fold in diameter. A tight iron-inducible expression system for T. versutus was successfully developed. The system was derived from fed-batch cultivation coupled with new design, build, test and validate (DPTV) approach. The inducible system was validated by toxin expression. Fed-batch cultivation coupled with DPTV approach could be applied to other autotrophs.